Phylogenetic analysis of the bee genus Capicola with the description of Capicola hantamensis sp. nov. (Hymenoptera: Dasypodaidae) - Michez, Denis; Kuhlmann, Michael (Zootaxa, 2007)
The genus Capicola Friese is one of the 8 genera included in the Dasypodaidae. Capicola contains 13 species (including the new species C. hantamensis sp. nov.) restricted to the xeric part of south-western Africa. New cladistic analysis and description of C. hantamensis sp. nov. complete the recent monographic revision of this genus (Michez et al. 2007) and demonstrate that the new species is the sister of all other Capicola.